Association of Bioelectrical Impedance Analysis–Derived Phase Angle and Sarcopenia in Older Adults. (2nd September 2016) - Kilic, Mustafa Kemal; Kizilarslanoglu, Muhammet Cemal; Arik, Gunes; Bolayir, Basak; Kara, Ozgur; Dogan Varan, Hacer; Sumer, Fatih; Kuyumcu, Mehmet Emin; Halil, Meltem; Ulger, Zekeriya
Abstract : Background: Sarcopenia is an important problem for older adults, leading to morbidity and mortality; therefore, early detection with a precise method is essential. We aimed to investigate the role of bioelectrical impedance analysis–derived phase angle as a determinant of sarcopenia. Materials and Methods: A cross section of 263 community‐dwelling and hospitalized older adults (>65 years) were assessed in terms of sarcopenia with bioelectrical indices and anthropometric measurements. Sarcopenic and nonsarcopenic groups were compared, and significant determinants of sarcopenia were further analyzed with multivariate logistic regression analysis. Results: Forty patients were diagnosed with sarcopenia. The following were significant correlates of sarcopenia: female sex, low weight/height, low body mass index, decreased muscle strength, low calf circumference, low skeletal muscle mass/index, high impedance at 50 kHz, a history of hypertension, worse nutrition status, and low phase angle. Diagnostic parameters with well‐known association were omitted, and sex, height, weight, body mass index, creatinine, nutrition status, phase angle, impedance at 50 kHz, and hypertension category were included in regression analysis. The following were independent associated factors with sarcopenia: phase angle (odds ratio [OR]: 0.59, 95% confidence interval [95% CI]: 0.40–0.87, P = .008), body mass index (OR: 0.84, 95% CI: 0.77–0.93, P = .001) impedance at 50 kHz (OR: 1.010, 95% CI: 1.006–1.015, P < .001), and height (OR: 0.93, 95% CI: 0.88–0.97, P = .001). Receiver operating characteristic analysis revealed that the optimal phase angle cutoff value to detect sarcopenia was ≤4.55º. Conclusions: Bioelectrical phase angle can be useful for diagnosis of sarcopenia.